Exploring Elements of Style in the Poem 'Drought': Unraveling the Layers of Meaning - Pariyar, Mamata Siwa; Bhujel, Sadikshya; Kushwaha, Sahil; Gyawali, Aarshi; Lama, Sumitra; Neupane, Dhruba Kumar (Baneshwor Campus Journal of Academia, 2024)
The poem "Drought" encapsulates the devastating impact of a prolonged dry spell on both the natural world and human society. Through vivid imagery, figurative language, and poignant diction, the poem portrays the bleak realities and emotional turmoil brought about by the absence of rain. The analysis explores the poem's elements of style, including its use of diction, figurative language, imagery, and syntax, to convey themes of despair, suffering, and resilience. Furthermore, from an epistemological perspective, the poem invites reflection on how knowledge is acquired and understood about the effects of drought, highlighting the complexities of human experience and the limitations of our understanding in the face of natural phenomena. Overall, "Drought" serves as a poignant exploration of the profound impact of environmental disasters and the enduring resilience of the human spirit.